Effects of Hydrological Regime on Foliar Decomposition and Nutrient Release in the Riparian Zone of the Three Gorges Reservoir, China - Chen, Zhangting; Arif, Muhammad; Wang, Chaoying; Chen, Xuemei; Li, Changxiao (Frontiers in Plant Science, 2021)
Foliar decomposition has significant effects on nutrient cycling and the productivity of riparian ecosystems, but studies on the impact of related hydrological dynamics have been lacking. Here, the litterbag method was carried out to compare decomposition and nutrient release characteristics in situ, including three foliage types [two single-species treatments using Taxodium distichum (L.) Rich., Salix matsudana Koidz., or a mixture with equal proportions of leaf mass], three flooding depths (unflooded, shallow flooding, and deep flooding), two hydrodynamic processes (continuous flooding and flooded-to-unflooded hydrological processes), and one hydrological cycle (one year) in the riparian zone of Three Gorges Reservoir. The results showed that both hydrological processes significantly promoted foliage decomposition, and all foliage types decomposed the fastest in a shallow flooding environment (P < 0.05). The mixed-species samples decomposed most quickly in the flooded hydrological process in the first half of the year and the unflooded hydrological process in the second half of the year. Flooding also significantly promoted the release of nutrients (P < 0.05). Mixed-species samples had the fastest release rates of carbon and nutrients in the flooded hydrological process in the first half of the year and the unflooded hydrological process in the second half of the year. Foliage decomposition was also closely related to environmental factors, such as water depth, temperature, and hydrological processes. Our research clarified the material cycling and energy flow process of the riparian ecosystem in the Three Gorges Reservoir area. It also provided a new reference for further understanding of foliage decomposition and nutrient release under different hydrological environments.